Konstrukční návrh brusky pro ostření pilových kotoučů - Tatíček, Vojtěch (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Tato práce je zaměřena na konstrukci brusky pilových kotoučů. Nejprve jsou důkladně probrány pilové kotouče a informace vhodné k dané problematice. Poté je navrhnuto několik možných variant řešení této brusky, z nichž je jedna vybrána a dále rozvinuta. Po provedení několika výpočtů jsou detailně rozebrány hlavní části modelu. Nakonec je zde uveden detailní postup práce na stroji včetně upínání pilového kotouče a nastavování řezných podmínek.

This thesis is focused on design of a grinding machine of saw blades. At first there are deeply talked over a saw blades and applicable information given for this problematic. After that there a few solutions of the grinding machine is suggested and one of them was chosen and developed. After solving a few calculations, the main part of the scale were deeply analysed and discussed. At the end there is stated detailed operating advancement of using the machine included fixing of saw blade and setting up a right grinding conditions.
Design of grinding machines circular saw blades
Keywords: Bruska pilových kotoučů; ostřička pilových kotoučů; ostření nástrojů; broušení zubů pilového kotouče; návrh manuální brusky.; Grinding machine of saw blades; saw blade sharpener; sharpening tools; grinding of saw teeth; design of manual grinding machine.